HUBUNGAN BUDAYA ORGANISASI DAN INSENTIF DENGAN KINERJA PERAWAT PELAKSANA DI RUANG RAWAT INAP RUMAH SAKIT UMUM HAJI MEDAN TAHUN 2023 - Yulia, Maya; Sarumpaet, Sorimuda; Sari, Nur Mala (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2025)
Organizational culture and incentives are factors that can affect the performance of organizational members in achieving organizational goals. One of the organizational members of the hospital is nurses who are the health workers with the largest proportion in the hospital and nurse performance plays an important role in providing health services. The aim of this study is to determine the relationship of organizational culture and incentives to the performance of executive nurses at RSU Haji Medan in 2023. This research design is a cross sectional study. The sample in this study were 92 nurses. Based on the results of statistical tests with Chi-square, there is a significant relationship between organizational culture of involvement with nurse performance with p-value = 0.002 and PR value = 6.87, between organizational culture of adjustment with nurse performance with p-value = 0.001 and PR value = 8.30, between organizational culture of consistency with nurse performance with p-value = 0.001 and PR value = 10.5, between organizational culture of mission with nurse performance with p-value = 0.001 and PR value = 20.0. There is no significant relationship between the criteria for providing incentives and nurse performance p-value = 0.346, and between the incentive delivery system and nurse performance p-value = 0.434, and it is found that the mission organizational culture variable is the strongest variable associated with nurse performance p-value = 0.001 and PR = 20.0. The hospital mission is more clearly socialized to all hospital employees, especially executive nurses, and nurses are expected to prepare and set strategies in carrying out the mission to achieve the long-term goals of the Haji Medan General Hospital.